Manufacture of concrete on the basis of modified finely dispersed peat - A. F. Kosach; I. N. Kuznecova; A. B. Demidov; J. V. Berezkina (Вестник СибАДИ)
The article dwells on the efficiency of manufacturing construction materials on the basis of vegetative and mineral compositions - peat. The raw materials base allows to consider the development of their production as one of the major directions in developing new progressive construction materials and innovative technologies in Khanty-Mansiysk Autonomous region. There are revealed and justified the possibility of using peat as a plasticized and hydrophobic organic substance on the basis of finely dispersed peat in fine grained concretes, the opportunity to regulate physical and mechanical qualities. On the basis of conducted research there is determined the dispersion degree, weight fraction of nanoparticles, quantative content of modified sandy-peat mixture up to 20 % of the concrete’s mass that decreases the thermal conduction coefficient by 10-12% and cement consumption by 15 % without decreasing strength properties of concrete.